Underage drinking and the role of parents. Issue 6 (7th February 2020) - Knopf, Alison
Abstract : Last week's article on underage drinking and DWIs touched on the role of parents in helping to prevent both (see "Binge drinking in 12th grade predicts DWIs, blackouts and 'extreme' binge drinking, " ADAW, Feb. 3, https://onlinelibrary.wiley.com/doi/10.1002/adaw.32610 ). The article was based on a study published in Pediatrics, co‐authored by Ralph W. Hingson, Sc.D., M.P.H., director of the Division of Epidemiology and Prevention Research at the National Institute on Alcohol Abuse and Alcoholism (NIAAA). Last week, Hingson, who presented on underage drinking at the annual leadership meeting of Community Anti‐Drug Coalitions of America (CADCA), also explained more about the role of parents. "Parents do have an influence over whether and how much their children drink, " he told us. For example, if a parent binge drinks, their children will be twice as likely to binge drink — and to have alcohol use disorder.